Effect of Short-Term Treatment with Continuous Positive Airway Pressure on Cardiopulmonary Exercise Tolerance, Pulmonary and Cardiac Function in Patients with Obstructive Sleep Apnea - Kondratavičienė, Laima; Padervinskienė, Lina; Lapinskas, Tomas; Ereminienė, Eglė; Malakauskas, Kęstutis; Žemaitis, Marius; Miliauskas, Skaidrius (Medicina (Kaunas, Lithuania), 2023)
Background: Obstructive sleep apnea (OSA) is a condition with a high prevalence, linked to an increased risk of cardiovascular disease as well as increased morbidity and death. CPAP is currently considered the “gold standard” treatment for OSA, but more thorough research and testing are required to assess its efficacy on cardiopulmonary function. Objectives: To evaluate pulmonary function of OSA patients, cardiopulmonary exercise tolerance test (CPET) performance, cardiac magnetic resonance imaging (MRI) parameters, and polysomnographic changes before and after 3 months of CPAP therapy. Materials and methods: A total of 34 patients diagnosed with moderate or severe OSA, as well as 17 patients as a control group for the evaluation of the cardiac MRI, were included in this study. All the subjects were obese (body mass index (BMI) > 30 kg/m2). Lung function tests, CPETs, cardiac MRIs, and polysomnography were performed at the time of the study’s enrolment before the initiation of the CPAP therapy and after 3 months of the CPAP treatment. Results: The patients‘ VO2max during the CPAP treatment tended to increase, but no statistical significance was found (before treatment it was 17.52 ± 3.79 mL/kg/min and after 3 months of treatment, it was 18.6 ± 3,4 mL/kg/min; p = 0.255). The CPAP treatment had positive effects on pulmonary ventilation at the anaerobic threshold (VEAT): 44.51 L/min (43.21%) during the baseline visit and 38.60 L/min (37.86%) after the 3-month treatment period (p = 0.028). The ventilator equivalent for the carbon dioxide slope (VE/VCO2) at peak exercise decreased from 23.47 to 20.63 (p = 0.042). The patients’ pulmonary function tests were without abnormalities and did not change after treatment. When assessing cardiac the MRIs, the RV ejection fraction was lower in the OSA group compared to that of the control subjects (53.69 ± 8.91 and 61.35 ± 9.08, p = 0.016). Both LA and RA global longitudinal strains (GLS) improved after 3 months of treatment with CPAP (20.45 ± 7.25 and 26.05 ± 14.00, p = 0.043; 21.04 ± 7.14 and 26.18 ± 7.17, p = 0.049, respectively). Additionally, it was found that CPAP therapy led to statistical improvements in RV end-diastolic volume (164.82 ± 32.57 and 180.16 ± 39.09, p = 0.042). The AHI and oxygen desaturation index (ODI) significantly changed after 3 months of the initiation of the CPAP treatment (p = 0.049 and p = 0.001, respectively). The REM sleep duration decreased, while the duration of non-REM sleep increased after treatment initiation with CPAP (p = 0.016 and p = 0.017, respectively). Conclusions: Short-term CPAP treatment improves pulmonary ventilation, sleep efficiency, and sleep architecture. Significant alterations in both atrias’ GLS and RV end-diastolic volume were observed after 3 months of treatment. Longer-term follow-up and a larger patient sample are needed to confirm the reproducibility of our results.